The social, cultural and environmental costs of hyper-connectivity : sleeping through the revolution - Hynes, Mike (Emerald Publishing Limited, 2021)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. This book seeks broader critical engagement with the design, development and adoption processes of contemporary digital technologies. Such technology has been the catalyst for great improvements in the fields of medicine, employment, education and communications. Yet, a new digital age has also brought a unique set of societal, cultural and environmental challenges that have yet to be fully understood and, when needed, confronted. It could be argued that aspirations to develop an information super-highway that would be an instrument for human flourishing, has given way to vast stores of worthless trivia and is hijacking our attention at every opportunity. In the absence of robust sociological input at the conceptual stages of digital communication technology development, the probability of these tools and instruments delivering change that is deeply personally, socially, culturally and environmentally damaging will continue to grow. Critical exploration of the organisational, social, political and environmental context of digital communications technology is necessary, without which technology will continue to be left 'to its own device' to determine the social and cultural values of societies, for better or worse. The Social, Cultural and Environmental Costs of Hyper-Connectivity investigates the profound effects 21st century digital technology is having on our individual and collective lives and seeks to confront the realities of a new digital age. Changes brought about by digital technology are frequently disruptive and, thus, need to be designed to protect against harm on society.